METAL OXIDE MONOBORIDES OF 3D TRANSITION SERIES BY QUANTUM COMPUTATIONAL METHODS (International Journal of Food and Nutritional Sciences, 2022)
In the present study the basic set B3LYP/ LanL2Dz level used and investigated 3d transitionmetal monoborides utilizing the density functional approach. The dimers, the lowest spinstate, bond length, vibrational frequencies are calculated. These dimers' cation and anion arealso investigated